Environmental Design and Neighborhood Context: A Multi-level Analysis of Crime at Apartments in Cincinnati Neighborhoods. (November 2021) - Deryol, Rustu; Payne, Troy
The present study examines the role of opportunity on crime counts within the multicontextual opportunity theoretical framework. We used weighted multilevel regression modeling of site observation data from a Cincinnati-based sample of 1003 apartments nested within 228 census block groups. Results indicate that only a couple of environmental design features are associated with crime in the expected direction, and some of these associations are neighborhood-context-dependent. We conclude that the results support the propositions of multicontextual opportunity theory suggesting that neighborhood level factors condition the relationship between micro level opportunity factors and crime. Since there is a scant literature on this topic, more research is needed to see if the findings hold true in other places.